Obesity induced T cell dysfunction and implications for cancer immunotherapy. (April 2018) - Aguilar, Ethan G; Murphy, William J
Highlights: Obesity leads to a state of metabolic and immune dysfunction. T cells are highly tuned by multiple intrinsic and extrinsic metabolic mechanisms. Obesity can alter the efficacy of emerging cancer immunotherapies. Abstract : Obesity has been shown to increase risk for a number of different disorders, including cancer. In addition, obesity is also associated with immune dysfunction, which could contribute to its strong association with other comorbidities. Recently, the immune system has been found to be heavily regulated by changes in metabolism. In particular, T cells are able to respond to intrinsic metabolic regulatory mechanisms, as well as extrinsic factors such as the changes in metabolite availability. The dysfunctional metabolic environment created by obesity could therefore have a direct impact on T cell responses. In this review, we highlight recent findings in the fields of T cell biology and obesity, with a focus on mechanisms driving T cell dysfunction and potential implications for immunotherapeutic treatment of cancer.